(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article examines the role of the family as a key social institution in strengthening family relations. It analyzes the impact of socio-economic and cultural changes, including globalization and digitalization, on family stability. The study highlights the educational function of the family, its role in transmitting values, and the need for comprehensive support of the family institution at the state and societal levels.